Selection of the Friction Model for Numerical Analyses of the Impact of Longitudinal Vibration on Stick-slip Movement - Marta Rybkiewicz (Advances in Science and Technology Research Journal, 2021)
The purpose of the experimental and numerical tests presented in this paper was to indicate a friction model suitable for simulation analyses of the impact of longitudinal tangential vibrations on stick-slip movement in sliding motion. The vibration parallel to the shift direction are forced in the contact zone of a shifted body and the base. They can cause partial or total reduction of the stick-slip phenomenon or even reduce the value of necessary drive force. The time characteristics of drive force were determined experimentally and in simulation for two cases, i.e. at a motionless or vibrating base. Simulation analyses were carried out in accordance with the described computational procedures implemented in Matlab-Simulink environment. Four models of friction were tested in the presented studies: Dahl, Karnopp, Reset Integrator and LuGre. Experimental tests were carried out on a specially designed tests stand. The Root Mean Square Error (RMSE) was used to compare the results of numerical calculations with results of experimental tests. The performed qualitative assessment and the determined RMSE values indicated that the LuGre and the Reset Integrator models ensure he best consistency of model and experimental time characteristics of the driving force.